Xenophobic Hate Speech on Social Media Through Messages Disseminated on the X Platform - Palella Stracuzzi, Santa; Sánchez Esparza, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The social network X facilitates the spread of hate speech. The Hatemedia project (2021-2024) examines hate expressions in digital environments linked to Spanish news media, using a Hate Monitor developed through data mining. A key result is a library categorizing five types of hate: general, political, sexual, misogynistic, and xenophobic. This study focuses on xenophobic messages on X from June to November 2024, highlighting the negative portrayal of immigrants. It concludes that these messages create a stigmatizing narrative, with news media significantly contributing to their dissemination, raising questions about editorial responsibility and content moderation policies.